Anokhina T. O. The ontological existence of silent lacunas - Anokhina T. O. (Philological Treatises, 2020)
The article deals with the communicative silence as the silent effect, which is exteriorized by the verbal and non-verbal markers in the belle-lettre discourse. As a discourse element, SE has the typical environment, situational model and style. SE has religious, philosophical and social sources and interdisciplinary commentary into that.